An investigation into seasonal power changes in collegiate baseball pitchers - Konz, S. M.; Lapole, C.; Anders, B.; Leigh, S. (ISBS Proceedings Archive (Michigan), 2023)
This study aimed to investigate changes in power and fatigue of collegiate baseball pitchers throughout a season to determine injury risk. Isokinetic, mobility, and performance test records were reviewed for 18 male NCAA-I baseball athletes. Testing was performed during the offseason, season start, and end of non-conference play and included medicine ball throws, hop testing, and 3-speed isokinetic testing. Statistical analysis determined that the kneeling medicine ball throw, 6-m hop, and several isokinetic outcomes decreased throughout the season. Using a combination of medicine ball throws, hop testing, and isokinetic testing at specific times during a season may provide insight into the overall fatigue level and injury risk within baseball pitchers.